Clinical genetic testing for male factor infertility: current applications and future directions. (7th April 2014) - Hotaling, J.; Carrell, D. T.
Summary Spermatogenesis involves the aggregated action of up to 2300 genes, any of which, could, potentially, provide targets for diagnostic tests of male factor infertility. Contrary to the previously proposed common variant hypothesis for common diseases such as male infertility, genome‐wide association studies and targeted gene sequencing in cohorts of infertile men have identified only a few gene polymorphisms that are associated with male infertility. Unfortunately, the search for genetic variants associated with male infertility is further hampered by the lack of viable animal models of human spermatogenesis, difficulty in robustly phenotyping infertile men and the complexity of pedigree studies in male factor infertility. In this review, we describe basic genetic principles involved in understanding the genetic basis of male infertility and examine the utility and proper clinical use of the proven genetic assays of male factor infertility, specifically Y chromosome microdeletions, chromosomal translocations, karyotype, cystic fibrosis transmembrane conductance regulator mutation analysis and sperm genetic tests. Unfortunately, these tests are only able to diagnose the cause of about 20% of male factor infertility. The remainder of the review will be devoted to examining novel tests and diagnostic tools that have the potential to explain the other 80% of male factor infertility that is currently classified as idiopathic. Those tests include epigenetic analysis of the spermatozoa and the evaluation of rare genetic variants and copy number variations in patients. Success in advancing to the implementation of such areas is not only dependent on technological advances in the laboratory, but also improved phenotyping in the clinic.